1996
DOI: 10.1002/pssa.2211560227
|View full text |Cite
|
Sign up to set email alerts
|

The influence of additional doping on the spectroscopic and scintillation parameters of PbWO4 crystals

Abstract: The Yb, ties structural peculiarities and the influence of additional doping of PbW04 crystals with Nb, Bi, and Mg ions have been investigated. It is shown that even a small amount of specific impurileads to an important redistribution of the structural point defects, the radiating centres, and their properties in the crystals. The data have been used for further optimization of PbW04 scintillator development for electromagnetic calorimeter (ECAL) of compact muon solenoid (CMS) at CERN. ') B.P. 110,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 8 publications
(4 reference statements)
0
28
1
Order By: Relevance
“…[20][21][22][23] For example, numerous experimental works directed at identifying several types of defects and their spectral roles in PWO have recently been published. [24][25][26][27][28][29] Particularly, there are discussions 30,31 over the contribution of color centers to the photoluminescence ͑PL͒ emission band, mainly to the green emission band. Groenink and Blasse 2 and Korzhik's group 4,7,32,33 concluded that the green emission originated from the ͑WO 3 + F͒ center in undoped PWO crystal, where F is an electron bound to a negative ion vacancy.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] For example, numerous experimental works directed at identifying several types of defects and their spectral roles in PWO have recently been published. [24][25][26][27][28][29] Particularly, there are discussions 30,31 over the contribution of color centers to the photoluminescence ͑PL͒ emission band, mainly to the green emission band. Groenink and Blasse 2 and Korzhik's group 4,7,32,33 concluded that the green emission originated from the ͑WO 3 + F͒ center in undoped PWO crystal, where F is an electron bound to a negative ion vacancy.…”
Section: Introductionmentioning
confidence: 99%
“…So the Mo 6+ ion is presented as an undesired impurity despite the fact that it can increase this material's light yield. Doping by Y 3+ and other selected trivalent ions is found to be the most effective tool for efficient suppression of trapping states, which take part in energy transfer and storage processes [11], or presumably substitute Pb 3+ ions [12] as well with pentevalent Nb-taking sites of tungsten atom [13].…”
Section: Introductionmentioning
confidence: 99%
“…Doping is another approach to artificially introduce local charge imbalance and thus compensate structure defects [9,10]. Early studies showed that doping by La 3+ and other selected trivalent ions is found to the most effective tool for efficient suppression of trapping states, which take part in energy transfer and storage processes [11], or presumably substitute Pb 3+ ions [12] as well as with pentevalent Nb taking sites of tungsten atom [13].…”
Section: Introductionmentioning
confidence: 99%